2020
DOI: 10.21733/ibad.789662
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelerde Algılanan Stres ve Stres Semptomlarının İşten Ayrılma Eğilimi Üzerindeki Etkisi

Abstract: The quality of healthcare services is correlated with happy healthcare professionals as well as the equipment used. However, stress is an important factor in working life, which negatively affects the productivity, happiness, job satisfaction, and consequently the private life of the staff and increases the tendency to leave. Nursing, which has the most intense working tempo of the occupational groups serving in the health sector, is the profession most affected by stress. It is possible to say that the main r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Çalışmada ilk olarak değişkenlere yönelik aritmetik ortalamalar incelenmiş ve en yüksek ortalamanın iş stresine ait olduğu gözlemlenmiştir. Bu bulgu daha önce sağlık çalışanları üzerine yapılan başka çalışmalarla paralel sonuçlar ortaya koymuştur (Erdilek Karabay, 2015;Uğan et al, 2018;Özüdoğru & Yıldırım, 2020;Çetin Aydın et al, 2020). Katılımcıların kişiörgüt uyumu, affetme ve iş tatminleri ise hemen hemen aynı ortalama düzeylerinde çıkmış, bu düzeylerin orta derecenin altında seyrettiği saptanmıştır.…”
Section: Sonuçunclassified
See 1 more Smart Citation
“…Çalışmada ilk olarak değişkenlere yönelik aritmetik ortalamalar incelenmiş ve en yüksek ortalamanın iş stresine ait olduğu gözlemlenmiştir. Bu bulgu daha önce sağlık çalışanları üzerine yapılan başka çalışmalarla paralel sonuçlar ortaya koymuştur (Erdilek Karabay, 2015;Uğan et al, 2018;Özüdoğru & Yıldırım, 2020;Çetin Aydın et al, 2020). Katılımcıların kişiörgüt uyumu, affetme ve iş tatminleri ise hemen hemen aynı ortalama düzeylerinde çıkmış, bu düzeylerin orta derecenin altında seyrettiği saptanmıştır.…”
Section: Sonuçunclassified
“…This finding has shown parallel results with other studies on healthcare professionals (Erdilek Karabay, 2015;Uğan et al, 2018;Özüdogru & İşletme Bilimi Dergisi (JOBS), 2021;9(3): 441-475. DOI: 10.22139/jobs.969491 Kişi-Örgüt Uyumunun İş Tatmini Ve İş Stresi Üzerine Etkisinde Affetmenin Aracı Rolü: 475 Yıldırım, 2020;Çetin Aydın et al, 2020). Person-organization fit, forgiveness and job satisfaction of the participants were at almost the same average levels, and it was determined that these levels were below the medium level.…”
mentioning
confidence: 99%
“…The most important problem of nurses in Turkey is the heavy workload due to insufficient employment, and the stress related to the nursing profession is an urgent issue that needs to be addressed (1,2). Nurses who work face-to-face with people due to their profession are negatively affected physically, mentally, socially and spiritually due to stress (3).…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies have shown that nursing is also a stressful profession. 2,3 In this regard, it is important to determine the personality characteristics nurses possess. According to Beck et al; 4 Beck (1983) mentions two personality dimensions in their cognitive theory; autonomy and sociotropy (social belonging).…”
Section: Introductionmentioning
confidence: 99%